2016
DOI: 10.1080/13621718.2015.1125406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the axial external magnetic field on copper/aluminium arc weld joining

Abstract: Pure copper and aluminium alloy was joined by cold metal transfer welding with the assistance of an axial external magnetic field in this work. The results reveal that magnetic field led to a reduction of the average heat input and improved the wetting behaviour of the weld metal on the copper sheet surface. The thickness of the Al 2 Cu intermetallic compound layer formed at the interface was decreased from 50 µm for normal welding to 5 µm for the magnetic field-assisted welding process. The joint strength was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Some researchers have also studied the effect of pulse current and pulse frequency on dissimilar welded joints. Liu and his research team outlined the application of a robot in a mass manufacturing environment with the help of an axisymmetric applied magnetic field in the weld zone of the lap joint with an overlap distance of 10 mm between a red copper T2 plate and an aluminum alloy 6061-T6 plate [74].…”
Section: Welding Of Copper To Aluminummentioning
confidence: 99%
“…Some researchers have also studied the effect of pulse current and pulse frequency on dissimilar welded joints. Liu and his research team outlined the application of a robot in a mass manufacturing environment with the help of an axisymmetric applied magnetic field in the weld zone of the lap joint with an overlap distance of 10 mm between a red copper T2 plate and an aluminum alloy 6061-T6 plate [74].…”
Section: Welding Of Copper To Aluminummentioning
confidence: 99%
“…This inhibition of IMC formation has also been seen in magnetic field‐assisted laser welding (MALW) of Al/steel [ 45 ] and Al/titanium. [ 46 ] The application of AMF in CMT welding of Cu and Al was found to lower the average heat input and the thickness of Al 2 Cu IMC, [ 47 ] as well as improve the joint strength. In the connection of 6061Al and pure titanium, [ 48 ] the AMF increases the wettability and fluidity of the welding wire, reduces the thickness of Ti 3 Al IMC, and improves the mechanical strength by 93.4%.…”
Section: Introductionmentioning
confidence: 99%
“…Schneider et al [10] found that porosity defects in the aluminium alloy were decreased obviously when the frequency and intensity of the alternating magnetic field were sufficient. Besides, influencing mechanism of magnetic field on welding has been studied by some scholars [11, 12]. The keyhole stability and energy distribution in molten pool could be changed by magnetic field.…”
Section: Introductionmentioning
confidence: 99%